Differential interactions of the antimicrobial peptide, RQ18, with phospholipids and cholesterol modulate its selectivity for microorganism membranes - Almeida, Claudiane V.; de Oliveira, Caio F.R.; dos Santos, Edson L.; dos Santos, Helder F.; Júnior, Edson C. [UNESP]; Marchetto, Reinaldo [UNESP]; da Cruz, Leticia A.; Ferreira, Alda Maria T.; Gomes, Valdirene M.; Taveira, Gabriel B.; Costa, Bruna O.; Franco, Octávio L.; et al. (Elsevier, 2021)
Background: Antimicrobial peptides (AMPs) are molecules with potential application for the treatment of microorganism infections. We, herein, describe the structure, activity, and mechanism of action of RQ18, an α-helical AMP that displays antimicrobial activity against Gram-positive and Gram-negative bacteria, and yeasts from the Candida genus. Methods: A physicochemical-guided design assisted by computer tools was used to obtain our lead peptide candidate, named RQ18. This peptide was assayed against Gram-positive and Gram-negative bacteria, yeasts, and mammalian cells to determine its selectivity index. The secondary structure and the mechanism of action of RQ18 were investigated using circular dichroism, large unilamellar vesicles, and molecular dynamic simulations. Results: RQ18 was not cytotoxic to human lung fibroblasts, peripheral blood mononuclear cells, red blood cells, or Vero cells at MIC values, exhibiting a high selectivity index. Circular dichroism analysis and molecular dynamic simulations revealed that RQ18 presents varying structural profiles in aqueous solution, TFE/water mixtures, SDS micelles, and lipid bilayers. The peptide was virtually unable to release carboxyfluorescein from large unilamellar vesicles composed of POPC/cholesterol, model that mimics the eukaryotic membrane, indicating that vesicles' net charges and the presence of cholesterol may be related with RQ18 selectivity for bacterial and fungal cell surfaces. Conclusions: RQ18 was characterized as a membrane-active peptide with dual antibacterial and antifungal activities, without compromising mammalian cells viability, thus reinforcing its therapeutic application. General significance: These results provide further insight into the complex process of AMPs interaction with biological membranes, in special with systems that mimic prokaryotic and eukaryotic cell surfaces.
Keywords: Antimicrobial peptides; Bacteria; Candida; Membrane selectivity